Gabon : Request for an Extended Arrangement Under the Extended Fund Facility-Press Release; Staff Report; and Statement by the Executive Director for Gabon. (IMF Staff Country Reports; Country Report ;, 2017)
This paper discusses Gabon's Request for an Extended Arrangement Under the Extended Fund Facility (EFF). The main goal of the program is to ensure macroeconomic stability and lay the basis for sustainable and equitable growth. To this end, the program seeks to ensure debt sustainability at the national level and help restore and preserve external stability at the regional level. It is built upon three pillars: (1) well-balanced fiscal consolidation that minimizes the impact on growth and protects vulnerable groups; (2) structural fiscal reforms to improve the efficiency and transparency of public spending; and (3) policies to enhance financial sector stability and economic diversification. The IMF staff supports the authorities' request for an extended arrangement under the EFF.